Associations of sedentary time, physical activity, and fitness with muscle glucose uptake in adults with metabolic syndrome. (22nd December 2022) - Garthwaite, Taru; Sjöros, Tanja; Laine, Saara; Koivumäki, Mikko; Vähä‐Ypyä, Henri; Eskola, Olli; Rajander, Johan; Kallio, Petri; Saarenhovi, Maria; Löyttyniemi, Eliisa; Sievänen, Harri; Houttu, Noora; et al.
Abstract : Objective: The objective of the study was to investigate the associations of sedentary time, physical activity, and cardiorespiratory fitness with skeletal muscle glucose uptake (GU). Methods: Sedentary time and physical activity were measured with accelerometers and VO2 max with cycle ergometry in 44 sedentary adults with metabolic syndrome. Thigh muscle GU was determined with [ 18 F]FDG‐PET imaging. Results: Sedentary time ( β = −0.374), standing ( β = 0.376), steps ( β = 0.351), and VO2 max ( β = 0.598) were associated with muscle GU when adjusted for sex, age, and accelerometer wear time. Adjustment for body fat‐% turned all associations non‐significant. Conclusion: Body composition is a more important determinant of muscle GU in this population than sedentary time, physical activity, or fitness.